Design Simulation of a Pedestrian Bridge Using Staad Pro Software for 2 Type of Common Bamboo Species - Isa, Muhammad Fitri Azrin; Mat Ropi, Ahmad Musyairi; Razlan, Muhammad Syafiq Ikhwan; Kesot, Mohd Jahaya (Multidisciplinary Applied Research and Innovation, 2023)
The study of design simulation using Staad Pro Software of a pedestrian bridge that 2 type of bamboo is being used as the main material. Ordinary materials like steel, concrete and timber particularly have been use in buildings and structures construction, thus this study focused on bamboo as the main material in construction. Bamboo is a species of flowering perennial plants in the Poaceae family in the subfamily of Bambusoideae. The bamboo tree’s structure is hollow and lacks xylem. The objective of this study was to do a simulation of pedestrian bridge using Staad Pro and knowing the usability of bamboos in structural construction, particularly pedestrian bridge. Moreover, the method of the simulation starts with design of the bridge, set up of material properties of the bamboo, loading and supports set up, and running the analysis. The preparation of the simulation design includes obtaining as much properties of the bamboo. Based on the findings, the bamboo is suitable to be use as the material of the pedestarian bridge based on the results, the results includes stresses of each beam in the Staad Pro which both type of bamboo does not exceed the tensile strength but exceed the compressive strength. The deflection of Dendrocalamus Asper’s bridge is 31.691 mm. Meanwhile, Bambusa Vulgaris’s bridge has deflection value of 45.049 mm which is higher than the evaluated limit, 40mm. These means that Dendrocalamus Asper pass the most results than Bambusa Vulgaris despite both having the potential to be success.